Antiferroelectric and ferroelectric orderings in frustrated chiral tilted smectics and a continuous change from anticlinic SmCA* to synclinic SmC* - VIJ, JAGDISH (My University, 2010)
In a frustrated binary-mixture system of ferroelectric and antiferroelectric liquid crystals, where the border line between SmCA* and SmC* in the temperature-concentration phase diagram runs almost parallel to the ordinate temperature axis, we have found a continuous change between them close to the critical concentration. The continuity has been confirmed as an intrinsic property in the bulk by observing almost perfect bell-shaped Bragg reflection bands due to the helicoidal director structure. The temperature variation of peak wavelength of the half-pitch band and, in particular, the characteristic disappearance of the full-pitch band apparently within the SmC* temperature region have been simulated with a change in the ratio of ferroelectric and antiferroelectric orderings. The observed continuous change has been described by the entropy effect in the 1D Ising model with the synclinic and anticlinic orderings as spins.
PUBLISHED
Keywords: Condensed matter physics; Ferroelectricity and antiferroelectricity; Nanoscience & Materials